Pojok Baca sebagai Inisiasi Sentra Edukasi Menumbuhkan Minat Baca - Muhammad Subardin; Imelda Imelda; Emylia Yuniarti; Suhel Suhel; Muhammad Teguh; Shelly Febriana Kartasari; Kurnia Sari (Jurnal Pemberdayaan Umat, 2023)
Purpose: The purpose of community service, first: to deliver education about the importance of reading as a source of knowledge and a means of information for PAUD students. The second objective is to provide management, administrative and technical assistance in the management of reading corners for the Pokja II Team for PKK administrators and PAUD administrators so that they can become a center for community education. Method: The method of implementing the activities is participatory empowerment and mentoring. The results of community service are the Reading Corner which occupies space in the village office with a number of books as many as 205 titles and has been equipped with SOPs for the management of the Reading Corner. PAUD students participated in educational activities very enthusiastically. Results: As many as 77 percent of the participants in technical training for the management of the Reading Corner understand enough and become more skilled at managing the Reading Corner. The limitation of community service lies in the time of implementation because it is carried out in a COVID-19 situation so that community mobility is hampered. Contribution: The contribution of community service plays a major role in the education level of the people of Ulak Kembahang II Village.